2018
DOI: 10.1074/jbc.tm117.000239
|View full text |Cite
|
Sign up to set email alerts
|

The redox requirements of proliferating mammalian cells

Abstract: Cell growth and division requires nutrients, and proliferating cells use a variety of sources to acquire the amino acids, lipids, and nucleotides that support macromolecule synthesis. Lipids are more reduced than other nutrients, whereas nucleotides and amino acids are typically more oxidized. Cells must therefore generate reducing and oxidizing (redox) equivalents to convert consumed nutrients into biosynthetic precursors. To that end, redox cofactor metabolism plays a central role in meeting cellular redox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 90 publications
2
92
0
Order By: Relevance
“…After exposure to 10 µM of MEK inhibitor, H295R cells presented a significantly higher lactate/alanine ratio and a higher mitochondrial membrane potential after 12 and 24 hours of treatment. The increased lactate/alanine ratio is associated with cellular redox state reflecting the intracellular NADH/NAD+equilibrium . The redox system is essential in maintaining cellular homeostasis and when a redox imbalance occurs, due to higher production of reactive oxygen species (ROS) or a decrease in endogenous protective antioxidants, cells become vulnerable to apoptosis and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…After exposure to 10 µM of MEK inhibitor, H295R cells presented a significantly higher lactate/alanine ratio and a higher mitochondrial membrane potential after 12 and 24 hours of treatment. The increased lactate/alanine ratio is associated with cellular redox state reflecting the intracellular NADH/NAD+equilibrium . The redox system is essential in maintaining cellular homeostasis and when a redox imbalance occurs, due to higher production of reactive oxygen species (ROS) or a decrease in endogenous protective antioxidants, cells become vulnerable to apoptosis and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 C). Given that fatty acid synthesis is highly NADPH-consuming (Fan et al, 2014; Hosios and Vander Heiden, 2018) and NADPH availability was reduced upon NNT loss, we hypothesized that these increases in fatty acid levels were resultant from increased uptake of exogenous fatty acids. Indeed, we found that NNT-deficient cells exhibited an increased capacity to take up a fluorescent palmitate analogue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A potential role for malic enzyme in pyruvate carboxylation suggests use of this enzyme to produce malate could be another pathway for TCA cycle anaplerosis. Of note, this reaction would require NADPH, and may be more favored in cancer cells that exhibit a reduced redox state (Hosios and Vander Heiden, 2018). We also considered phosphoenolpyruvate carboxykinase (PEPCK) or malic enzymes 2 and 3 as possible contributors to pyruvate carboxylation activity, although these reactions are less energetically favorable in the reverse direction in comparison to malic enzyme 1; malic enzyme 1 is cytosolic, which is thought to be a more reducing environment than the mitochondria where malic enzymes 2 and 3 are localized (Hu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%